THE NOTEWORTHINESS OF EPICUREAN ETHICS IN WES ANDERSON’S THE WONDERFUL STORY OF HENRY SUGAR - Yasmine Azzah Adillah Wirnoto; Raddine Salsabiyla; Asjad Nina Hanan Ramadhani; Lisma Ayu Arditha; Hariyono; Rommel Utungga Pasopati (LPPM Universitas PGRI Adi Buana, 2025)
This study looks at The Wonderful Story of Henry Sugar (2023) by Wes Anderson through the lens of Epicurean ethics. It shows how the movie deals with ideas, things, money, and right and wrong. Anderson shows Henry Sugar’s change from selfishness motivated by greed to selflessness urged by kindness by adapting a Yogi’s experience. This study uses qualitative explorative methods and textual analysis to find out how Epicurean ideas like ataraxia (peace of mind), moderation of desire, and the search for worthwhile pleasure can be seen in Sugar’s moral journey. The movie criticizes capitalist ideas by showing how useless it is to collect things and stressing the importance of living a moral life, being kind, and being simple. Overall, this study says that Anderson’s adaptation not only brings Dahl’s moral story to life again, but it also uses Epicurean ethics as a way to think about modern problems of desire, ideology, and moral responsibility.